2014
DOI: 10.12693/aphyspola.126.392
|View full text |Cite
|
Sign up to set email alerts
|

Application of Extended Jiles-Atherton Model for Modelling the Influence of Stresses on Magnetic Characteristics of the Construction Steel

Abstract: Paper presents the possibility of application of the Jiles-Atherton extended model to describe the magnetic characteristics of construction steel C45 under the inuence of tensile stresses. Experiment was performed on the frame-shaped samples. Then, the inuence of stresses on hysteresis loops was modelled with the Jiles-Atherton extended model. The obtained results of the modelling are consistent with results of the experimental measurements. The results of modelling create new possibilities of explanation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 13 publications
1
9
0
1
Order By: Relevance
“…However, the case of f 500 Hz is preferable from technical point of view because of smaller noise amplitude to induced voltage value ratio. The observed magnitude of AC µ r relative changes remains in qualitative accordance with reported data [9] concerning Jiles-Atherton model DC parameters for C45 steel, however these parameters exhibit nonmonotonic behavior when stress exceeds Villari point (ca. 120 MPa).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…However, the case of f 500 Hz is preferable from technical point of view because of smaller noise amplitude to induced voltage value ratio. The observed magnitude of AC µ r relative changes remains in qualitative accordance with reported data [9] concerning Jiles-Atherton model DC parameters for C45 steel, however these parameters exhibit nonmonotonic behavior when stress exceeds Villari point (ca. 120 MPa).…”
Section: Resultssupporting
confidence: 91%
“…The source of magnetostriction is strain dependence of magneto-crystalline anisotropy originating from the spin-orbital coupling of electrons. The variety of magneto-mechanical effects in bulk material and thin films was reported both in historical papers [2,3] and in more recent ones [4][5][6][7][8][9]. These phenomena can be utilized for determining magnetoelastic parameters of materials [8] as well as for nondestructive evaluation (NDE) of mechanical elements [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years the interest of scientific community in the study of magneto-mechanical effects for diagnostics purposes is clearly noticeable [7,18,[23][24][25][26][27]. Historically, most probably the first attempt to avail of magnetic methods in order to determine residual stress in cylindrical metal bars was undertaken in 1971 by Abuku and Cullity, who have carried out a number of measurements of the reversible effective permeability at different bias field strengths for nickel and steel rods and concluded that this quantity increases almost linearly with tensile stress [28].…”
Section: Discussionmentioning
confidence: 99%
“…Evolutionary strategies, especially (µ+λ) evolutionary strategy were successfully applied previously for determination of Jiles-Atherton model parameters [23]. Such methods of optimization are able to escape from local minima.…”
Section: Evolutionary Strategiesmentioning
confidence: 99%